NFLUENCE OF UNIVERSITY NETWORK STRUCTURES ON FORMING THE NETWORK ENVIRONMENT OF REGIONAL ECONOMY (on the example of national research universities of Tatarstan Republic) - D. A. Kaibiyainen (Russian Journal of Economics and Law)
Objective: to elaborate theoretical and applied aspects of the processes of forming the new network institutional environment of the Russian regional economy under the influence of the developing integral educational network structures (basing on the study of the experience of national research universities of Tatarstan Republic) Methods: general scientific logical methods of analysis and synthesis, induction and deduction, scientific abstraction, as well as the method of systemic-functional analysis. ISSN 1993-047X. «Актуальные проблемы экономики и права». 2015. № 1 Экономика и управление народным хозяйством Results: the practical examples are revealed and analyzed of introducing the new network integral principles into the functioning of national research universities, which have a real economic effect and influencing such indicators of regional economy as the growth of employment, reduction of unemployment, etc. Scientific novelty: problems of network structures development in the Russian education have not been thoroughly studied yet. The article analyzes the experience, reveals and describes the methods and techniques of forming the network educational structures in the functioning of national research universities in Tatarstan Republic Practical value: the author shows the ability of network university structures not only to play a significant role forming the new institutional environment of the regional economy, but also to influence the macro- and microeconomic indicators of development of the region and the country.